The Use of Negative Acceleration as Accessory Force during Lifting - Jordan Trafimow; Alexander S. Aruin (Advances in Orthopedics)
Objectives. Injury associated with lifting, especially low back injury, is a big problem in industry that accounts for loss of work and high medical expenses. Studies of biomechanics of lifting provide a basis for optimization of lifting. The aim of the study was to further investigate the role of the upward force due to negative acceleration during a lift. Methods. Nine healthy subjects lifted an empty box and a box with additional load of 10, 20, and 25 lb. Kinematic data were recorded during the lifts and accelerations were calculated, and angular positions of the trunk and knee were obtained during the lifting when negative accelerations were used. Results. Negative acceleration assisted the quadriceps when the thighs were at approximately 90° and the hips when the trunk was rotating toward standing position. Negative acceleration was present during lifts of different loads. Conclusion. The outcome of the study suggests that enhancing the use of negative acceleration could be a strategy to improve the quality of lifting and minimize a probability of low back injury.